ANALYSIS INFLUENCE OF SERVICE QUALITY TO BEHAVIORAL INTENTION WITH SATISFACTION AS AN INTERVENING VARIABLE - Khakim, Luqman -; Murtiasri, Eka - (Politeknik Negeri Semarang, 2017)
ABSTRACTThe purpose of this study was to determine the significance of the influence of service quality to behavioral intention of Museum Manusia Purba Sangiran touristswith satisfaction as an intervening variable. Analysis tool utilized is the path analysis.Samples taken were 314 respondents and set up purposive sampling method. Based on the results obtained found that the variable quality of service and traveler satisfaction significant positive effect on behavioral intention travelers Museum Manusia Purba Sangiran. Satisfaction as intervening variables have a significant influence on the intention tourist behavior and value is more dominant than the quality of service.Â Keywords: Service quality, Satisfaction, Behavior intentionÂ ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui signifikansi pengaruh kualitas pelayanan terhadap niat perilaku Museum Manusia Purba Sangiran terhadap kepuasan wisatawan sebagai variabel intervening. Alat analisis yang digunakan adalah analisis jalur. Contoh yang diambil adalah 314 responden dan menyusun metode purposive sampling. Berdasarkan hasil yang diperoleh diketahui bahwa variabel kualitas pelayanan dan kepuasan wisatawan berpengaruh positif signifikan terhadap perilaku wisatawan pelancong Museum Manusia Purba Sangiran. Kepuasan sebagai variabel intervening berpengaruh signifikan terhadap perilaku dan nilai wisatawan yang lebih dominan daripada kualitas pelayanan.Â Kata kunci: Kualitas layanan; Kepuasan; Niat berperilaku